Knockdown of LINC01614 inhibits lung adenocarcinoma cell progression by up‐regulating miR‐217 and down‐regulating FOXP1. Issue 9 (22nd June 2018) - Liu, Ai‐Na; Qu, Hua‐Jun; Yu, Cai‐Yan; Sun, Ping
Abstract: We tried to identify the function of LINC01614 in lung adenocarcinoma (LUAD) and reveal its underlying mechanisms. qRT‐PCR was applied to assess the expression of LINC016014 in LUAD tissues, noncancerous tissues and cells. Through colony formation assay, MTT assay and apoptosis analysis, we examined the variation of cell proliferation and apoptosis ability after silencing LINC01614. Moreover, the targeting interactions among LINC01614, miR‐217 and FOXP1 were validated via luciferase reporter assay, and then, we regulated the expression of miR‐217 and FOXP1 to ascertain their importance in cell proliferation and apoptosis. LINC01614 and FOXP1 were found to be up‐regulated in LUAD tumours and cells, whereas miR‐217 was down‐regulated. The experiment showed that target‐specific selectivity exists between LINC01614‐miR‐217 and miR‐217‐ FOXP1 3′UTR. Furthermore, we disclosed that inhibition of LINC01614 could activate miR‐217, which subsequently restrained FOXP1 . It was proved that LINC01614 promoted FOXP1 by inhibiting miR‐217, which ultimately stimulated the development of LUAD.